Solid‐Phase Epitaxial Growth of A‐Site‐Ordered Perovskite Sr4−xErxCo4O12−δ: A Room Temperature Ferrimagnetic p‐Type Semiconductor. (26th October 2015) - Katase, Takayoshi; Takahashi, Hidefumi; Tohei, Tetsuya; Suzuki, Yuki; Yamanouchi, Michihiko; Ikuhara, Yuichi; Terasaki, Ichiro; Ohta, Hiromichi
Abstract : The oxygen‐deficient Sr4− x Er x Co4 O12− δ (SECO), one of the ordered perovskite oxides, is a room‐temperature (RT) ferrimagnetic semiconductor that arises from the A‐site‐ordered structure. Development of such a material can lead to the realization of spintronic heterojunction devices; however, to this point there have been difficulties in achieving the A‐site‐ordered structure in SECO thin films. Here, single‐crystalline film growth of SECO with perfectly aligned A‐site‐ordered structure on (LaAlO3 )0.3 (Sr2 TaAlO6 )0.7 substrates by solid‐phase epitaxy (SPE) method is demonstrated. The brownmillerite‐type, A‐site‐disordered structure of the as‐grown epitaxial film clearly changes into well‐aligned A‐site‐ordered structure after heat treatment at 1050 °C in air; the aligned ordered structure in the film is clearly visualized at atomic level. This ordering induces ferrimagnetism with Curie temperature ( T c ) ≈310 K and it is found that the SECO film with p‐type semiconductivity exhibits anomalous Hall effect at the temperature up to 300 K, which is suitable for the test bench to demonstrate advanced spintronic heterojunction devices, operating at RT. The present SPE method is expected to serve as a powerful technique for the fabrication of thin films and exploration of potential characteristics of A‐site‐ordered perovskite oxides. Abstract : Solid‐phase epitaxial growth of A‐site‐ordered perovskite Sr4− x Er x Co4 O12− δ (SECO), a room‐temperature (RT) ferrimagnetic p‐type semiconductor, is demonstrated. The A‐site‐ordered SECO film with p‐type semiconductivity exhibits anomalous Hall effect at RT, which is promising for the development of heterojunction devices of spintronics.